Peace-Oriented Dakwah and Peacebuilding: A Critical Discourse Analysis in Conflict-Affected Middle East Societies - Hamid, Abdul; Firdaus, M.; Uyuni, Badrah; Farooq, Hafiz Shuaib (Jurnal Ilmiah Peuradeun, 2025)
Prolonged conflicts in the Middle East have created an urgent need for culturally-grounded peacebuilding strategies, within which Islamic preaching (dakwah) emerges as a potential medium for fostering reconciliation—though its discursive mechanisms remain understudied. This study investigates how dakwah constructs peace-oriented discourse in conflict-affected societies, including Palestine, Syria, and Iraq, by examining its linguistic, narrative, and ideological dimensions. Employing a qualitative critical case study design and Van Dijk’s Critical Discourse Analysis (CDA), we analyzed over sixty sermons, digital content, and interviews with preachers and peace actors from 2021 to 2024. The findings reveal that dakwah actively constructs counter-narratives of justice, compassion, and reconciliation; employs rhetorical strategies such as inclusive pronouns, healing metaphors, and jihad reinterpretation to reframe conflict and promote social cohesion; and positions religious actors as cultural mediators who utilize both sermons and digital platforms to disseminate peace messages. The study concludes that dakwah serves as a transformative form of communication capable of challenging hegemonic conflict narratives. It further proposes a novel CDA-Based Peace Dakwah Framework, offering scholars and practitioners an interdisciplinary tool for peacebuilding, conflict resolution, and Islamic communication studies. This replicable model highlights the potential of religious discourse as soft power in global peacebuilding efforts.